2019
DOI: 10.1021/acsabm.9b00627
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Aggregation Studies of a Pyridothiazole-Based AIEE Probe and Its Application in Sensing Amyloid Fibrillation

Abstract: We report the aggregation and photophysical properties of a pyridothiazole-based, aggregation-induced, emission-enhancement (AIEE) luminogen 4-(5-methoxy-thiazolo­[4,5-b]­pyridin-2-yl)­benzoic acid (PTC1) and its application for the sensitive detection and monitoring of amyloid fibrillation. The aggregation properties of the AIEE probe were extensively studied by atomic force microscopy (AFM) and dynamic light scattering (DLS), and it was noted that as aggregation increases the fluorescence of PTC1 also was in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…(AgNPs) over diatom surface for making high efficiency dye synthesized solar cell (DSSC) and hence can be used as potential devices forrenewable & sustainable energy sources . The presence of non‐covalent forces facilitate the self assembling phenomenon of multifunctional short peptide conjugates and amino acids over diatom and other biological cell surfaces . Ultra short peptide and amino acid‐based organic biomaterial potentially interacts with membrane proteins and hence quickly respond towards the biological cells which make them favorable biomaterial for surface modification or biofabrication for numerous biological applications …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…(AgNPs) over diatom surface for making high efficiency dye synthesized solar cell (DSSC) and hence can be used as potential devices forrenewable & sustainable energy sources . The presence of non‐covalent forces facilitate the self assembling phenomenon of multifunctional short peptide conjugates and amino acids over diatom and other biological cell surfaces . Ultra short peptide and amino acid‐based organic biomaterial potentially interacts with membrane proteins and hence quickly respond towards the biological cells which make them favorable biomaterial for surface modification or biofabrication for numerous biological applications …”
Section: Figurementioning
confidence: 99%
“…[44] The presence of non-covalent forces facilitate the self assembling phenomenon of multifunctional short peptide conjugates and amino acids over diatom and other biological cell surfaces. [45][46][47][48][49][50][51] Ultra short peptide and amino acid-based organic biomaterial potentially interacts with membrane proteins and hence quickly respond towards the biological cells which make them favorable biomaterial for surface modification or biofabrication for numerous biological applications. [52][53] In this work, we have investigated the self-assembly of Ltyrosine alone and in the presence of bioactive zinc metal ions followed by deposition of these hybrid nanostructures over diatom surface for biological applications.…”
mentioning
confidence: 99%
“…Self-assembly is a process through which molecules assemble to well-ordered structures through non-covalent interactions via bottom-up-approach. 1,2 The main driving force responsible for the formation of self-assembled structure are non-covalent interactions like hydrogen bonding, 3,4 vander waals force, 5,6 electrostatic interaction, 7,8 pi-pi stacking, 9,10 and hydrophobic interactions. 11,12 The study of formation of supramolecular architectures through the process of self-assembly of biomolecules is particularly crucial due to its wide range of application in various fields such as material science, 13,14 biology, 15,16 chemistry, 17,18 biomedical engineering, 5,19 tissue engineering, 20,21 sensor designing, 22,23 and nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…32 In another study mechanical properties of Fmocdiphenylalanine were studied 33 and also the self-assembly of Fmoc-peptides was used for the preparation of nanostructures and hydrogels, 34 Our group has been interested in assessing the self-assembling properties of single amino acids, 3,35 peptides, [36][37][38] and heterocyclic compounds. 10,[38][39][40][41][42] Recently, we reported selfassembled structure formation of cysteine and methionine and its amyloid like characteristic. 3 In other study our group has also reported the self-assembled structure formed by proline, hydroxyproline 35 and lysine.HCl.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Ni II also affecting the sPA2 morphology and cluster of fibrous morphologya long with small circularly arranged fibres were obtained( Figure 5D). In the presenceo fC u II and Zn II the fibres are nucleating and therefore appeared as hairy supermicelles 50 Next we would like to check the effect of prolonged incubation on the sample of sPA-M n + hybrid structures.O ur observations revealed that the 12 hi ncubation furtherr efined the morphology of the poorly resolved sPA-M n + hybrid structures followed by promoting robustness of these structures.H ighly resolved and refined morphology were seen for all the hybrid structures. Upon prolonged incubation the sPA1-Fe III solution produced fractal like self-assembly with thickness of 5-15 nm and micrometers in length (Figure6A).…”
mentioning
confidence: 99%